2009
DOI: 10.4049/jimmunol.0802217
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 2 Interaction with TLR2 Is Required for Efficient Innate Immune Responses to Mycobacteria via Cathelicidin Expression

Abstract: Gp91phox/NADPH oxidase (NOX) 2 is the main catalytic component of NOX, which mediates the phagocytic killing of ingested pathogens via the production of reactive oxygen species (ROS). However, Mycobacterium tuberculosis (Mtb) is relatively resistant to the microbicidal effects of ROS. Thus, the exact roles of NOX2 in the innate immune control against Mtb infection are not fully resolved. In this study, we show that NOX2 is essential for TLR2-dependent inflammatory responses and 1,25-dihydroxyvitamin D3 (1,25D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 51 publications
8
160
1
3
Order By: Relevance
“…Recent reports have shown that Mycobacterium stimulates TLR2 receptors, and that TLR2 interacts with Nox-2 to produce ROS. 25 However, our results showed that Nox-1 expression is strongly induced by HKLM, suggesting that Nox-1 plays an essential role in ROS production caused by TLR2. While resveratrol dramatically inhibited Nox-1 expression, ROS production only decreased partially, suggesting the presence of other ROS sources.…”
Section: Discussioncontrasting
confidence: 46%
“…Recent reports have shown that Mycobacterium stimulates TLR2 receptors, and that TLR2 interacts with Nox-2 to produce ROS. 25 However, our results showed that Nox-1 expression is strongly induced by HKLM, suggesting that Nox-1 plays an essential role in ROS production caused by TLR2. While resveratrol dramatically inhibited Nox-1 expression, ROS production only decreased partially, suggesting the presence of other ROS sources.…”
Section: Discussioncontrasting
confidence: 46%
“…Cathelicidin is an antimicrobial peptide expressed in response to TLR2 stimuli and vitamin D treatment in a process also involving Gp91(phox)/NADPH oxidase (NOX2, Table 1 (IV)) [67]. Among vitamin D receptor (VDR)-regulated genes, cathelicidin plays a critical role during TB [68].…”
Section: Antimycobacterial Mechanisms and Lysosomal Functionsmentioning
confidence: 99%
“…The role of vitamin D(3)-dependent gene expression in both WT and iNOS /-mice during TB has been established [67]. Cathelicidin is an antimicrobial peptide expressed in response to TLR2 stimuli and vitamin D treatment in a process also involving Gp91(phox)/NADPH oxidase (NOX2, Table 1 (IV)) [67].…”
Section: Antimycobacterial Mechanisms and Lysosomal Functionsmentioning
confidence: 99%
“…phox , TLR3, TRIF, and STAT1 knockout (KO) mice (on the C57BL/6 background), as described previously (16,18). Briefly, bone marrow cells from the femur and tibia were cultured for 4-5 d in DMEM (Life Technologies BRL) containing M-CSF (25 ng/ml), 4 mM glutamine, and 10% FBS.…”
Section: Mice and Cellsmentioning
confidence: 99%
“…phox /NADPH oxidase (NOX)2 plays an essential role in TLR2-dependent inflammatory responses and antimicrobial activity against mycobacteria (16). Additionally, TLR4-dependent ROS generation is essential for mammalian innate immunity by acting through the TRAF6/ASK1/ p38 axis (17).…”
mentioning
confidence: 99%